2013
DOI: 10.1590/0103-6440201302115
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxicity of White MTA, MTA Fillapex® and Portland Cement on Human Periodontal Ligament Fibroblasts

Abstract: The aim of this study was to compare the in vitro cytotoxicity of white mineral trioxide aggregate (MTA), MTA Fillapex ® and Portland cement (PC) on human cultured periodontal ligament fibroblasts. Periodontal ligament fibroblast culture was established and the cells were used for cytotoxic tests after the fourth passage. Cell density was set at 1.25 x10 4 cells/well in 96-well plates. Endodontic material extracts were prepared by placing sealer/ cement specimens (5x3mm) in 1mL of culture medium for 72 h. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 25 publications
4
69
0
9
Order By: Relevance
“…As it was corroborated by the SEM results in the same period, it is possible to notice some free areas or some cells with circular morphology. Probably, this effect is related to the addition of components to MTA Fillapex, such as resin composites like the salicylate (14) or other pigments, which may have increased the toxic effect, because in contact with cells, these soluble chemicals may lead to cell modification (24).…”
Section: Discussionmentioning
confidence: 99%
“…As it was corroborated by the SEM results in the same period, it is possible to notice some free areas or some cells with circular morphology. Probably, this effect is related to the addition of components to MTA Fillapex, such as resin composites like the salicylate (14) or other pigments, which may have increased the toxic effect, because in contact with cells, these soluble chemicals may lead to cell modification (24).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies (CHANG et al, 1998;CAMARGO et al, 2009;SEPET et al, 2009;SILVA et al, 2012A;SILVA et al, 2012B;YOSHINO et al, 2013) used fibroblasts for quick and easy growth (HIRSHMAN et al, 2012), in addition to their availability in periapical tissues and the periodontal ligament, which are areas that are susceptible to the effects of intracanal medications and their degradation products (YOSHINO et al, 2013). Fibroblasts are also the largest producers of collagen tissue and, therefore, actively participate in the repair tissue process (SILVA et al, 2012B).…”
Section: Discussionmentioning
confidence: 99%
“…After each experimental period, the cytotoxicity was analyzed using 20 µl/well MTT solution (Sigma ® , St. Louis, MO, USA) at a concentration of 5 mg/mL for 4 hours (YOSHINO et al, 2013). The formazan that formed during this period was dissolved by adding 100 mL of acidified isopropanol solution with 0.04 M/l HCl to each well and shaking the culture plate for 30 minutes ).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…257 MTA sealers show greater toxicity than AH Plus. 258 . In a four-week study, MTA Fillapex showed continual cytotoxicity.…”
Section: Cytotoxicity (Iso 10993-3)mentioning
confidence: 99%